PENINGKATAN HASIL DAN EFISIENSI USAHATANI BUDIDAYA PADI SAWAH DENGAN SISTEM TANAM BENIH LANGSUNG (TABELA) - Hartono, Rudi; Gunawan, Gunawan (Jurnal AGRISEP, 2004)
Paddy still has the strategic  role as staple food, so that effort to increase  of its productivity  become the attention various related parties.  Continuously productivity  pushed the researcher  to study that has high product system efficiency in order to increase  earnings  of farmer and continuing  farming system.  Farming  system  that depressed  the production  cost through use fertilize according  to land fertility per plant of tabela system  disease  operation pest by PHT and exploiting of farm resource.  Study of tabela  system  paddy  rice  field was executed  in Countryside  Rimbo  Recap,  Sub district  Curup, Regency  Rejang  Lebong broadly  carpet  50 ha entangling  45 cooperator  farmer. Location  selected  by purposive  with the consideration  that area represent  central paddy in regency of Rejang L(jbong.  Varieties used are IR 64. Direct seed plantsystem show a prospect by economizing  labor used from 28 to 20 HOC, Increasing  production  of O.5 -  1.15 tontha either due manifestly  can economize  the labor from 28 becoming  10 HOC, increase  product  0, 5 - 1,5 ton / ha dry shell of rice harvest.  dry shell of rice eliminating  negative  impact of seedbed  and quality of shell rice and also short crop age 11 - 17 day  which  is enlarge  the  opportunity   of  increase  per  plant  intensity.   This existence  of great  productivity  and  farmer earnings whiCh is to 15 - 20 % can be obtained by through product increase  wide  association  and cost-saving  production like labor fee,  expense fertilize and also opportunity  of exploiting farm resource